PRETERM BIRTH AND LOW BIRTH WEIGHT IN SINGLETON PREGNANCIES AFTER IN VITRO FERTILIZATION- INFLUENCE OF INFERTILITY AND METHOD OF FERTILIZATION - Sergei Slavov; Galina Yaneva (Peytchinski Publishing, 2021)
The aim of our study was to determine the effect of infertility and the method of fertilization on the frequency of preterm birth and low birth weight in singleton pregnancies achieved by in vitro fertilization (IVF). The study was conducted in the period 01.2013 - 12.2017 and included 286 patients with births from singleton IVF pregnancies. Classical IVF received 107 patients (group A1) and ICSI fertilization - 148 (group A2). Cases with tubal infertility were 81 (group B1), and 85 were with male infertility (group B2). In group A1, birth prior to 37 weeks of gestation (w.g.) was found in 33 (30.8%) cases, compared to 26 (17.6%) in group A2 (p=0.029).In group A1, birth weight <2500 g was observed in 27 (25.3%) of cases, and in group A2 - in 17 (11.5%) of cases (p=0.015). In group B1, birth prior to 37 w.g. was established in 26 (32.1%) of the cases, compared to 9 (10.6%) in group B2 (p=0.003). In group B1 there was birth weight <2500 g in 19 (23.5%) of patients, compared to 6 (7.1%) in group B2 (p = 0.009). The average weight of the newborn and average duration of pregnancy was lower in groups with IVF fertilization and tubal infertility compared to ICSI fertilization and male infertility. Tubal infertility and classical IVF fertilization are independent risk factors that increase the frequency of preterm birth and low birth weight in IVF singleton pregnancies.